Path Analysis Tingkat Pengangguran Terbuka dan Kemiskinan di Kabupaten Langkat - Harahap, Muhammad Arfan; Hasibuan, Sri Wahyuni (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
Unemployment and poverty remain persistent issues that governments, especially regional administrations, continuously strive to address. The analysis of unemployment and poverty varies across regions due to different datasets. This study reveals the latest data related to research variables in Langkat Regency. Path analysis was employed to accurately measure the influence of variables through intervening variables with dynamic macroeconomic data. The regression model in sub-structural 1 indicates a direct influence of economic growth and inflation on unemployment, showing a combined effect of 65%. Furthermore, the sub-structural regression model 2 reveals a direct influence of unemployment on poverty, while economic growth and inflation do not directly affect poverty. However, collectively, economic growth, inflation, and unemployment show an influence of 85%. Other findings using path analysis demonstrate an indirect influence of economic growth and inflation on poverty through unemployment. These results enrich the literature on unemployment and poverty and provide new data for similar studies across various regions in Indonesia. These findings are expected to contribute to the literature on policy-making related to unemployment reduction and poverty alleviation in the macroeconomic context of Langkat Regency.